2009
DOI: 10.1088/0953-8984/21/14/145803
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetic properties of Fe-doped ZnO prepared by the sol–gel method

Abstract: Zn(0.97)Fe(0.03)O nanoparticles were synthesized by the sol-gel method. X-ray diffraction (XRD) and transmission electron microscope (TEM) analysis revealed that the samples had pure ZnO wurtzite structure and Fe ions were well incorporated into the ZnO crystal lattice. X-ray photoelectron spectroscopy (XPS) showed that both Fe(2+) and Fe(3+) existed in Zn(0.97)Fe(0.03)O. The result of x-ray absorption near-edge structure (XANES) further testified that Fe ions took the place of Zn sites in our samples. Magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 23 publications
2
42
0
Order By: Relevance
“…A high temperature ferromagnetism was reported numerously for Co doped ZnO in thin films produced by all accessible methods including pulsed layer deposition [7], the magnetron co-sputtering [8], the solgel method [9], and epitaxial thin films [10]. Recently, Fe doped ZnO nanostructures, synthesized by the sol-gel method, were observed to be ferromagnetic [11]. The observed room temperature ferromagnetism was reported to be an intrinsic Fe doped ZnO property.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A high temperature ferromagnetism was reported numerously for Co doped ZnO in thin films produced by all accessible methods including pulsed layer deposition [7], the magnetron co-sputtering [8], the solgel method [9], and epitaxial thin films [10]. Recently, Fe doped ZnO nanostructures, synthesized by the sol-gel method, were observed to be ferromagnetic [11]. The observed room temperature ferromagnetism was reported to be an intrinsic Fe doped ZnO property.…”
Section: Introductionmentioning
confidence: 95%
“…The observed room temperature ferromagnetism was reported to be an intrinsic Fe doped ZnO property. Interestingly, neither Fe, nor FeO and Fe 2 O 3 phase in the Fe doped ZnO nanoparticles were observed based on X-ray absorption near edge structure measurements [11]. On the other hand, there are report claiming no essential role of the transition metals in the ZnO magnetism in low dimension Fe and Mn doped ZnO films [12].…”
Section: Introductionmentioning
confidence: 99%
“…Fe occupying the substitutional sites are in 2+ state while the surface Zn vacancies and oxygen interstitial facilitate the Fe 3+ state. 24 Since the as-grown ZAF thin film is expected to have more defects near the surface, it is likely to have a higher concentration of Fe 3+ which mediates the transfer of electrons from the enzyme's active site to the external circuit directly via co-doped ZnO thin film. Inhibition of redox peak is observed on immobilization of GOx and is attributed to its macro-molecular structure of non-conducting nature proving to be a hindrance in charge transfer (figure 5).…”
mentioning
confidence: 99%
“…2(e (13.3 eV). 24 Therefore, the valence state of Fe ions in the Fe-doped ZnO sample is believed to be þ3.…”
Section: Structural Analysismentioning
confidence: 99%
“…doped ZnO could endow a certain ferromagnetism to ZnO. [24][25][26][27][28] For example, Liu et al 24 synthesized Fe-doped ZnO nanoparticles by a sol-gel method and found that the nanoparticles showed typical ferromagnetism. El-Hilo et al 26 synthesized Nidoped ZnO powders by thermal co-decomposition of a mixture of bis(acetylacetonato)zinc(II)hydrate and bis(dimethylglyoximato)nickel(II) complexes and observed that the powders presented a ferromagnetic behavior at room temperature.…”
Section: Introductionmentioning
confidence: 99%